Investigation of the Spatial and Temporal Variations in the External Nutrient Loads of Lake Ziway in Relation to the Effects of Climatic and Hydrological Factors - Tibebe, Dessie; Kassa, Yezbie; Lemma, Brook; Zewge, Feleke (International Journal of Chemistry and Materials Research, 2020)
Excess household wastes from settlements, agrochemical and industrial effluentsfromthe watershed into Lake Ziway can pause a great problem in Lake Ziway. This study was therefore conducted to analysis the amount dynamics, and influences the external and internal household wastes, agrochemical and industrial loads, on Lake Ziway ecosystem. Water samples were collected on a monthly basis from nine sampling sites of the lake for the analysis of some selected water quality parameters in 2014 and 2015 in different seasons. The physicochemical parameters were measured in-situ with portable multimeter and nutrients were according to the APHA [1]. The inflows from Katar and Meki Rivers indicate the main external nutrient sources of the lake ecosystem. The study showed a general trend of higher external nutrient load in the wet than in the dry seasons. These high nutrient loads indicate the susceptibility of Lake Ziway toapproach Eutrophication levels. Person Correlation indicated that precipitation, water level, discharge flow and air temperature had weak to strong positive correlations with SRP, TP, TIN and TN,while DO, pH, EC, total alkalinity (TA) and soluble reactive silica (SiO2-Si) were negatively correlated with water level and discharge outflows. In order to minimize more pollution of the lake water quality and to eventually restore the lake, management of fertilizers and pesticide usage in the lake watershed should be given urgent priority.